2015
DOI: 10.1590/1414-431x20144300
|View full text |Cite
|
Sign up to set email alerts
|

Tissue hyaluronan expression, as reflected in the sputum of lung cancer patients, is an indicator of malignancy

Abstract: Hyaluronan (HA) shows promise for detecting cancerous change in pleural effusion and urine. However, there is uncertainty about the localization of HA in tumor tissue and its relationship with different histological types and other components of the extracellular matrix, such as angiogenesis. We evaluated the association between HA and degree of malignancy through expression in lung tumor tissue and sputum. Tumoral tissue had significantly increased HA compared to normal tissue. Strong HA staining intensity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
(46 reference statements)
4
27
0
1
Order By: Relevance
“…[16,70,71] The current study indicated a strong intensity of stromal and tumoral HA expression was significantly (p < .05) associated with the presence of nodal metastasis. A similar finding was reported by Wernicke et al, Suwiwat et al, Afify et al [16,56,[70][71][72] Regarding incidence of recurrence, 58.6% of cases with a positive history of recurrence revealed strong tumor and stromal HA expression but was not statistically significant by chi-square test (p values .06 and .07). Kaplan Meier curves demonstrated a statistically significant difference of stromal HA intensity of expression in relation to DFS (p = .050).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[16,70,71] The current study indicated a strong intensity of stromal and tumoral HA expression was significantly (p < .05) associated with the presence of nodal metastasis. A similar finding was reported by Wernicke et al, Suwiwat et al, Afify et al [16,56,[70][71][72] Regarding incidence of recurrence, 58.6% of cases with a positive history of recurrence revealed strong tumor and stromal HA expression but was not statistically significant by chi-square test (p values .06 and .07). Kaplan Meier curves demonstrated a statistically significant difference of stromal HA intensity of expression in relation to DFS (p = .050).…”
Section: Discussionsupporting
confidence: 86%
“…[54] Also, previous few studies reported high levels of in HNSCC. [55,56] In contrast, the HA expression is low in melanoma, and its absence is significantly correlated with the metastatic potential. [57,58] Accumulation of HA can decrease tumorigenic potential and confer resistance to cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HA levels can be increased around the tumor cells themselves or within the tumor stroma (Itano, Zhuo, & Kimata, ). However, as with other highly differentiated tumors such as lung, breast, colon and prostate cancer, astrocytomas express increased amounts of HA in both tumor epithelia and intratumoral areas (Boregowda et al, ; Josefsson et al, ; Misra et al, ; Rangel et al, ; Schwertfeger, Cowman, Telmer, Turley, & McCarthy, ; Wiranowska & Rojiani, ).…”
Section: The Brain Extracellular Matrix and Its Interaction With Gliomentioning
confidence: 99%
“…Tese de doutorado -USP Em diversos tipos de câncer, proteínas intracelulares e de MEC têm se mostrado como potenciais marcadores diagnósticos presentes em secreções, principalmente no sangue, na saliva, no escarro e na urina (Melo et al, 2015;Franzmann et al, 2011;Rangel et al, 2015;Paserotti et al, 2006).…”
Section: Maristela Peres Rangel Tese De Doutorado -Uspunclassified